The Kidfluencer Phenomenon and Modern Slavery: A Critical Analysis of Indonesia's Legal Framework in Protecting Children from Digital Exploitation - Lubis, Alvan Rahfiansyah (HM Publisher, 2025)
The digital era has ushered in unprecedented opportunities for children to engage with online platforms. However, this increased accessibility has also exposed them to new forms of exploitation, including the